2009
DOI: 10.1021/nl803443x
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and Photoresponse Properties of an Intramolecular p-n Homojunction in Single Phosphorus-Doped ZnO Nanowires

Abstract: The single-crystal n-type and p-type ZnO nanowires (NWs) were synthesized via a chemical vapor deposition method, where phosphorus pentoxide was used as the dopant source. The electrical and photoluminescence studies reveal that phosphorus-doped ZnO NWs (ZnO:P NWs) can be changed from n-type to p-type with increasing P concentration. Furthermore, we report for the first time the formation of an intramolecular p-n homojunction in a single ZnO:P NW. The p-n junction diode has a high on/off current ratio of 2.5 x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
69
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 37 publications
1
69
1
Order By: Relevance
“…Liu et al [276] reported a series of measurements on a ZnO-NW-based FET device, which has response to visible light under different environments (air, vacuum, N 2 , and O 2 ). ZnO:P NWs can play an important and significant role in optoelectronics, since these NWs can be changed from n-type to p-type with an increase in phosphorus concentration [277]. If a feasible and rapid process is developed to dope ZnO NWs with higher concentration, it would rapidly change the way that ZnO NW PDs are deployed in complex systems.…”
Section: ) Recent Development and Future Prospectsmentioning
confidence: 99%
“…Liu et al [276] reported a series of measurements on a ZnO-NW-based FET device, which has response to visible light under different environments (air, vacuum, N 2 , and O 2 ). ZnO:P NWs can play an important and significant role in optoelectronics, since these NWs can be changed from n-type to p-type with an increase in phosphorus concentration [277]. If a feasible and rapid process is developed to dope ZnO NWs with higher concentration, it would rapidly change the way that ZnO NW PDs are deployed in complex systems.…”
Section: ) Recent Development and Future Prospectsmentioning
confidence: 99%
“…Fabrication of one-dimensional ZnO is found to be an efficient solution to improve its photodetection and photoresponse performance. Meanwhile, various nanostructures including heterostructures [16], homojunctions [17], nanocomposites [18, 19], and ZnO of special morphologies [20] have also been sequentially reported which could furtherly shorten the rise and decay time of ZnO-based UV detectors. By comparison, n-ZnO/n-GaN isotype heterojunctions have been proven to be a superior choice owing to their similar crystal structure, lattice parameter, and wide band gaps (3.37 eV for ZnO and 3.39 eV for GaN), which could generate carriers from the interior localized states excited by light or electric field.…”
Section: Introductionmentioning
confidence: 99%
“…To fabricate high quality ZnO micro/nanostructure devices, the growth of reproducible and high quality p-type ZnO is very important. However, there have many reasons make p-type acceptor doping of ZnO very difficult, including low solubility of acceptor dopants, self-compensation, deep level of impurities and structural instability [7][8][9]. So, in order to realize ZnO optoelectronic device, an alternative approach is fabrication of heterojunctions and Schottky contacts on n-ZnO micro/nanostructures [10].…”
Section: Introductionmentioning
confidence: 99%